Tentativa católica de modernidade: o conceito de pessoa humana e sua realização histórica (1960-1980) - Costa, Lucas Aparecido [UNESP] (2014)
The present doctor‟s thesis, entitled Catholic attempt of modernity: the concept of human person and its historic achievement aims to demonstrate how the Social Doctrine of the Church (DSI) established, between 1960 and 1980, its concept of the human person. It is necessary to focus, however, that the Catholic idea about the man was carried in the period prior to the arch of time bounded in this research, precisely in the pontificates of Leo XIII, Pius XI and Pius XII. In Brazil, the concept of human dignity expressed in Catholic social teaching incorporated and guided the practice of Catholic laity and sectors of the ecclesiastical hierarchy, roughly, progressives, at two different times of the decades of 1960 and 1970. We have, on the first occasion, the existence of the Catholic University Youth (JUC) and the social movement and weekly Brazil, Urgent (1961-1964), which, in order to justify their policy options, made use of precepts originating in social Catholicism - reference is made to the contribution of L. J. Lebret, E. Mounier and, above all, J. Maritain. In the subsequent decade, the presence of Catholic sectors intending to justify his course of action in the Social Doctrine of the Church, was shown in the position of certain bishops and at work, in São Paulo, the Basic Ecclesial Communities (CEBs) and the Worker Pastoral (PO).The attempt of putting into practice ideas from social Catholicism is understood in this thesis as a bet of many laymen and even significant fractions of the ecclesiastical hierarchy, to solve the problem of the human person. This path, which involved clergy and faithful, had as an orientation the proposal of a Catholic attempt of modernity, in which two ways of being Church crisscrossed over the decades of 1960 and 1970